Medical Biotechnology - Glick, Bernard R.; Delovitch, T. L.; Patten, Cheryl L. (ASM Books, 2014)
In this jargon-free, easy-to-read textbook, the authors demystify the discipline of medical biotechnology and present a roadmap that provides a fundamental understanding of the wide-ranging approaches pursued by scientists to diagnose, prevent, and treat medical conditions. This book is written to educate premed and medical students, dental students, pharmacists, optometrists, nurses, nutritionists, genetic counselors, hospital administrators, and individuals who are stakeholders in the understanding and advancement of biotechnology and its impact on the practice of modern medicine.